USABILITY TESTING ON THE POINT OF SALES SHARIA APPLICATIONS: KAASHIR - Nasrizal Akbar; Asri Suangga; Rini Lestari; Edi Sukarmanto; Rudy Hartanto; Andhika Anandya (Kajian Akuntansi, 2025)
This research aims to carry out Usability Testing on the Kaashir Application. Usability Testing is a method of evaluating the usability of software that aims to increase the usability of an application/product by conducting analysis, identifying problems, measuring efficiency, measuring convenience, and determining user satisfaction. Usability Testing is carried out on the Kaashir application to determine the ease of use of the application, such as ease of understanding features and memory of feature locations. Several stages must be carried out in carrying out Usability Testing, namely conducting research on the application, preparing recitation scenarios, looking for respondents or testing subjects, creating a standard questionnaire, and carrying out usability analysis of the results of respondents and questionnaires. Based on the results of this research, it was concluded that Kaashir has an excellent level of ease to learn and understand. The efficiency in speeding up work, especially recording stock and sales, is also outstanding. Apart from that, the various features in this application are also easy to remember, with a very good level of user satisfaction. As an application that is still in the development process, there are not many errors in this application. Errors that occur are easy to overcome.